PENGEMBANGAN MEDIA ULTAPUPA TERHADAP PENGETAHUAN PESERTA DIDIK PADA MATERI PANCAINDRA KELAS IV SEKOLAH DASAR - Dwi Anggraini Setyaningrum; Raden Wisnu Wijaya Dewojati (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
Science learning in elementary schools still uses lecture methods and textbooks, making students less active and easily bored, especially in the five senses material. This condition has an impact on low student interest and involvement in understanding the relationship between the form and function of the five senses. This study aims to develop innovative learning media in the form of Pop-Up Snakes and Ladders for the Five Senses (Ultapupa) which is designed to improve the knowledge of fourth-grade students and create a more interesting and interactive learning experience. This study uses the Research and Development (R&D) method with the ADDIE model which includes five stages: analysis, design, development, implementation, and evaluation. The media developed is a 60x60 cm snakes and ladders game board with pop-up elements, question cards, material cards, pawns, dice, and game instructions. The product was validated by media experts, material experts, and learning experts, then tested in a limited trial with teachers and fourth-grade students of Muhammadiyah Sambisari Elementary School. Data were collected through questionnaires, interviews, observations, and qualitative and quantitative assessments. The results showed that Ultapupa was declared very suitable for use. Expert validation was rated very good, while teacher and student feedback was positive. This medium has been shown to increase student engagement and understanding of the five-sensory material.